Efektivitas Pelayanan Perizinan Berbasis Teknologi Informasi di DPMPTSP Lombok Tengah - Putri Rahmadani; Muhammad Sawir; Pardamean Daulay (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
The advancement of information technology has encouraged governments to develop digital-based public services to enhance efficiency, transparency, and accessibility. One of the key implementations is the electronically integrated business licensing system known as the Online Single Submission (OSS). The Investment and One-Stop Integrated Service Office (DPMPTSP) of Central Lombok Regency has adopted this system as an innovation in licensing services. However, its implementation still faces several challenges, including technical issues, limited digital infrastructure, and the readiness of human resources. This study aims to analyze the effectiveness of information technology-based licensing services at the DPMPTSP of Central Lombok Regency. A qualitative method with a descriptive approach was employed, involving interviews with 32 informants consisting of officials, staff, and service users. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings indicate that the implementation of IT-based licensing services has generally been effective. Based on the five service quality indicators proposed by Parasuraman—tangibles, reliability, responsiveness, empathy, and assurance—only the responsiveness dimension has not been optimal. This is primarily due to low digital literacy among the public and the limited responsiveness of staff in addressing service complaints. Furthermore, other constraints include uneven internet infrastructure, concerns over data security and public trust, lack of assistance during the digital registration process, and insufficient socialization and public education.